Hard and unreal advice mothers, social science, and the Victorian poverty experts - Martin, Kathleen Callanan (Palgrave Macmillan, 2008)
This is the first detailed and systematic study of the social science of poverty as practiced by the Victorian experts who had so much influence on relief policy in this area, and who were among the founders of British social science. The book examines what they knew, or what they thought they knew, about the poor.
Includes bibliographical references and index
Keywords: Geschichte 1800-1900; Geschichte; Politik; Poverty -- Research -- Great Britain -- History -- 19th century; Poor -- Government policy -- Great Britain -- History -- 19th century; Regierung; Armut; Großbritannien